Pilgrimage and political economy: translating the sacred - Eade, John; Coleman, Simon (Berghahn Books, 2018)
Pilgrimage and political economy : introduction to a research agenda / Simon Coleman and John Eade -- From the Indian Ganges to a Mauritian lake : Hindu pilgrimage in a 'diasporic' context / Mathieu Claveyrolas -- Transnational courting through Shakyamuni Buddha : Japanese pilgrimage and geographical dowries in North India / David Geary -- Sufism and pilgrimage market : a political economy of a shrine in southern Pakistan / Remy Delage -- Allah always hears the prayers of a traveller : nationalized shrines and transnational imaginaries in Bukhara / Maria Louw -- 'Pilgrimage capital' and Bosnian Croat pilgrimage places : Bosnian Croat pilgrimages and transnational ties through time and space / Mario Katic -- Translating Catholic pilgrimage sites into energy grammar : contested spiritual practices in Chartres and Vezelay / Anna Fedele -- A Pentecostal shrine in Mexico : ethnography of migration and pilgrimage / Patricia Fortuny Loret de Mola -- The paths of Saint James in Brazil : body, spirituality and market / Carlos Alberto Steil -- Afterword : going beyond the elusive nature of pilgrimage / Dionigi Albera